Advances in stress cardiac MRI and computed tomography. (September 2013) - Hamirani, Yasmin S; Kramer, Christopher M
Stress cardiac MRI and stress computed tomography (CT) perfusion are relatively new, noninvasive cardiovascular stress-testing modalities. Both of these tests have undergone rapid technical improvements. Data from randomized controlled trials in stress cardiac MRI are becoming gradually incorporated into cardiovascular clinical practice, not only to assess physiological significance of coronary artery disease, but also to provide prognostic information. As CT perfusion protocols become more uniform with adequate handling of artifacts and decreasing radiation exposure with combined CT coronary angiography/CT perfusion imaging, it has the potential to become a comprehensive diagnostic test.